Control of Circadian Change of Serotonin N-Acetyltransferase Activity in the Pineal Organ by the β-Adrenergic Receptor - Deguchi, Takeo (1972)
Serotonin N-acetyltransferase (EC 2.3.1.5) activity in the rat pineal organ is enhanced 50-fold at night. Rats exposed to light at night or kept in darkness during the daytime do not show any elevation of enzyme activity. Treatment with reserpine, a compound that depletes norepinephrine from nerves, 1-propranolol, a β-adrenergic blocking agent, or cycloheximide, an inhibitor of protein synthesis, abolishes the nocturnal increase in serotonin N-acetyltransferase activity, indicating that the enzyme activity is modulated by neural release of norepinephrine from sympathetic nerves via β-adrenergic receptors, and that the increase in enzyme activity is due to synthesis of new enzyme molecules. When rats are exposed to light at night or injected with 1-propranolol, there is a precipitous fall in serotonin N-acetyltransferase activity (half-life 5 min). Cycloheximide administered at night results in a slow fall in enzyme activity (half-life 60 min). When rats are kept in darkness and then exposed to light for 10 min, L-isoproterenol rapidly initiates the elevation of serotonin N-acetyltransferase activity to the initial level in 60 min. On the other hand, when the rats are kept in continuous light, L-isoproterenol initiates an increase in serotonin N-acetyltransferase activity after a lag phase of 60 min. The results indicate that there are two types of changes in serotonin N-acetyltransferase activity; a rapid increase and decrease mediated by the β-adrenergic receptor, and a slow increase and decrease in enzyme activity that appears to represent the turnover of the enzyme.